Association between accelerometer-measured physical activity and mortality in cancer survivors: A prospective cohort study from UK Biobank - Zhihan Jiang; Bingyan Wang; Yifei Zhao; Jing Weng; Jiaojiao Liao; Liyuan Tao; Kui Sun; Zhipeng Zhang; Xin Zhou; Wei Fu (The Journal of Nutrition, Health and Aging)
Objectives: Postdiagnosis physical activity is an important component of healthy lifestyle in cancer survivors. In this study, we aimed to explore the association between intensity and duration of physical activity measured by wearable accelerometers and mortality among pan-cancer survivors. Methods: A prospective cohort study involving cancer survivors (n = 11,708) from UK Biobank was performed. All participants had thorough physical activity data that was measured by wrist-worn accelerometers. Restricted cubic splines and multivariate Cox proportional hazards models were employed to assess the dose-response associations between physical activity time at varying intensities and both all-cause and cancer-specific mortality. Results: During a median follow-up of 8.9 years, a total of 983 deaths occurred, including 656 cancer-related deaths. Multivariate models identified significant dose-response associations between moderate to vigorous-intensity physical activity (MVPA) time and mortality. Hazard ratios (HRs) for all-cause mortality were 0.64 (95% CI, 0.54–0.76), 0.61 (95% CI, 0.51–0.74) and 0.52 (95% CI, 0.42–0.66) in participants with MVPA time of 272–407, 407–579 and ≥579 min per week, respectively. HRs for cancer-specific mortality were 0.71 (95% CI, 0.58–0.88), 0.69 (95%CI, 0.55–0.87) and 0.61 (95%CI, 0.47–0.81) for the aforementioned groups. Similar patterns were observed for moderate-intensity physical activity but not for light-intensity physical activity. Survival benefits of active physical activity were pronounced in cancers from multiple organs. Conclusions: Active physical activity substantially reduced all-cause mortality in pan-cancer survivors and cancer-specific mortality in cancer survivors of specific sites. However, the benefits were significant only when intensity of physical activity reached moderate to vigorous level.